Use of the e-book in the educational process A survey study of faculty members at the Institute of Management / Rusafa for the academic year 2013/2014 (Journal of the College of Basic Education, 2022)
The research aims to introduce the electronic book as one of the important electronic information sources used in university libraries and information centers. It highlights its most prominent features, its importance in university education, the forms of its design, and its reading devices.